A ferrovia no norte do Rio Grande do Sul: uma história do trecho Passo Fundo-Marcelino Ramos/RS (1957-1997) - Kerber, Aline Asturian (2017)
This dissertation analyzes the history of the railroad in the north of the State of Rio Grande do Sul by studying the stretch between Passo Fundo and Marcelino Ramos. For this, it takes up the history of the railroad implantation in the north of the State in the early twentieth century and its role in that historical moment. Its emphasis, however, is the economic and social role of the railroad in the period in which the Rede Ferroviária Federal S.A. was responsible for the administration of the railways in the country, that is, from 1957 to 1997. In addition, it seeks to understand the historical local and national contexts that culminated in the deactivation of the railway section from Passo Fundo to Marcelino Ramos in 1997. It will analyze why rail transportation did not become an element of regional development throughout the decades in the north of Rio Grande do Sul and also as an element of national integration, a function that has long been performed by highways. The sources used in the research include the press, oral interviews and official documents issued by the Rio Grande do Sul government and federal government and its agencies. This research takes place in the perspective of regional history with emphasis on the areas that had their economies and their stories linked to the railroad. By studying the history of a specific railway section, it seeks broader reflections and an understanding of wider historical processes. Thus, it is understood that the study of the history of the proposed section is significant not only for the understanding of the local history, but it makes possible to understand the conjunctures that involve the history of rail transportation in the national level, since it brings numerous elements that are representative of historical processes and broader contexts. Among these contexts we can mention the introduction of capitalist logic in regions far from the economic centers of the country, with the construction of railways with foreign capital being one of the elements used in this purpose; the growth of the importance of road transportation concerning to railroads during the twentieth century; privatizations and concessions of public services in the 1990s, among them rail transportation; and the deactivations of countless railway sections across the country after its concessions to private enterprise.